Análisis del cooperativismo agrícola (kibutz) como modelo para el desarrollo del buen vivir en ecuador; kibutz yotvata en el consejo regional Hevel Eilot - Israel durante el año 2013 – 2015 - Morales Peneida, Diana Estefania (2015)
This document was prepared with the purpose of providing an alternative or model of working together for small Ecuadorian farmers who currently work in a disorganized way. The fundamental idea of the thesis consists of the importance that the cooperative model represents Kibbutz, its possibilities and alternatives for achieving the "Sumak Kawsay". The first chapter presents an overview of the emergence of cooperativism, contributions of its major precursors, cooperative outstanding models who succeeded them and a light outline of its development in other countries. The second chapter shows the organizational structure of the Yotvata Kibbutz. The third chapter focuses on the development of cooperativism in the Ecuador. The fourth chapter focuses on the "Sumak Kawsay" as a concept of good living for the development of society. Finally, in the fifth chapter the conclusions and recommendations resulting from the development of this work are.